2020
DOI: 10.1049/iet-sen.2019.0041
|View full text |Cite
|
Sign up to set email alerts
|

Academic approach to transform organisations: one engineer at a time

Abstract: Every year software development industry requires a higher number of trained software engineers who are not only skilled programmers but also talented software projects managers. To deliver high-quality software projects, engineers require of the application of sound engineering competencies along with discipline. Obtaining those practices usually require years of experience. Companies are not prepared to invest this time on engineers resulting in a high percentage of deficient projects. Here, the authors pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…In such conditions, the educator was monitoring student progress and facilitating understanding through discussions [61]. A educator as facilitator was also seen as the person strengthening communication, ethics, leadership, security and software skills [44]. These conditions point to educators as the agents in charge of developing student‐centred learning environments [87].…”
Section: Resultsmentioning
confidence: 99%
“…In such conditions, the educator was monitoring student progress and facilitating understanding through discussions [61]. A educator as facilitator was also seen as the person strengthening communication, ethics, leadership, security and software skills [44]. These conditions point to educators as the agents in charge of developing student‐centred learning environments [87].…”
Section: Resultsmentioning
confidence: 99%
“…When it comes to teachers, a number of studies emphasize that implementing active learning methods requires great effort from them as well as a lot of time resources [65,70]. Likewise, because the biggest share of learning depends on students, they need to invest a considerably large amount of time in developing the solution, which often leads to spending more hours on it than is originally planned in the curriculum [71]. It is reported that because of time constraints, students often feel like they have to rush through developing a solution, which does not ensure that they deliver the best result at their capability [44].…”
Section: Findings 41 Barriers and Challenges Of Implementing Active L...mentioning
confidence: 99%
“…In PBL, PjBL, and CBL, students work within teams, and because of different students' roles and team compositions, conflicts are normally difficult to avoid, and often it is up to the teacher to monitor and help solve them [65]. Studies report that students find it challenging to work within teams not only because of potential issues of fair work distribution but also because typically teams in PBL, PjBL, and CBL are multidisciplinary [71]. Moreover, because of the nature of team compositions, students might be struggling to pick up the pace of developing the necessary skills and solving the problem or challenge [62].…”
Section: Findings 41 Barriers and Challenges Of Implementing Active L...mentioning
confidence: 99%
See 2 more Smart Citations